(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
In this work we will deal with the occupations that preceded the current Cajazeiras Housing Complex, located in the Miolo region of the city of Salvador, highlighting some memories and speeches built about the neighborhood of Águas Claras. We will observe how the image of a rural region within an urban area of ​​the city of Salvador was woven over this locality and the changes that were brought about by the construction of Housing Complexes of the Cajazeira Project. In view of this, we will analyze how such stigmas are attributed to poor neighborhoods, especially to slums and informal settlements, transforming such regions into a danger to the interests of the Military Dictatorship that ended between the 1970s and 1980s. Key-words: Águas Claras. Memory. History of cities. Urban segregation.